2016
DOI: 10.1080/02772248.2015.1133818
|View full text |Cite
|
Sign up to set email alerts
|

International standardized procedures for in vivo evaluation of multi-walled carbon nanotube toxicity in water

Abstract: The classical approach in ecotoxicological evaluation of chemical substances consists of conducting standardized bioassays on organism models. In this work, the potential impact of industrial multiwalled carbon nanotubes was investigated by ecotoxicological standardized procedures using aquatic organisms of different trophic levels, namely bacteria, green algae, invertebrates, fish, and amphibians. The results indicated (1) inhibition of growth in amphibians at 50 mg L ¡1 and higher, and (2) no effects on daph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Moreover, MWCNTs were unstable, formed aggregates and settled out of the exposure dispersion removing any co-adsorbed algal cells (Table 1; Figure 3A). The co-adsorption of CNTs and other CNMs to algal cells in exposure studies is well documented (Schwab et al, 2011, Long et al, 2012, Sørensen et al, 2015, Mouchet et al, 2016, Nolte et al, 2017. Critically, co-adsorption prevents separation of the two matrix elements, e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, MWCNTs were unstable, formed aggregates and settled out of the exposure dispersion removing any co-adsorbed algal cells (Table 1; Figure 3A). The co-adsorption of CNTs and other CNMs to algal cells in exposure studies is well documented (Schwab et al, 2011, Long et al, 2012, Sørensen et al, 2015, Mouchet et al, 2016, Nolte et al, 2017. Critically, co-adsorption prevents separation of the two matrix elements, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…However, two key limitations regarding the applicability of OECD 201 to MNMs have been identified. The first is that the chelating agent EDTA, a component of the test medium, can interfere with metallic MNMs causing iron precipitation and resulting in unfavourable growth conditions (Kadar et al, 2012, Hund-Rinke et al, 2016, Mouchet et al, 2016, Zhang et al, 2016. It is now recommended that an EDTA-free algal medium should be considered when testing metal MNMs (Hund-Rinke et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Chronic toxicity studies on aquatic organisms have been reported for other CNMs, including fullerene (C 60 ), 21 singlewalled carbon nanotube (SWCNT), 22 and multi-walled carbon nanotube (MWCNT). 23,24 Nevertheless, the possible chronic and adverse effects of GN on aquatic organisms is nearly unknown. Thus, it is necessary to conduct chronic toxicity tests to evaluate the real toxicity of GN materials in aquatic systems.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, size is known as one of the main parameters modulating particle toxicity. These effects have already been demonstrated in Xenopus in the case of exposure to carbon nanoparticles, for example [ 48 , 49 ]. This toxicity can be qualified as direct when it is mechanical or indirect when it is nutritional.…”
Section: Discussionmentioning
confidence: 81%